2021
DOI: 10.1016/j.heliyon.2021.e06960
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and mental well-being of long-distance hikers: A quantitative and qualitative approach

Abstract: Hikers performing long distances (1000-5500 kms a year) were analyzed using quantitative and qualitative methods to evaluate their mental well-being and to find their motivation as well as to analyze the excessive physical activity. 112 hikers completed a questionnaire (M (age) ¼ 40.28, SD ¼ 8.77, 57.1% male) and 25 individuals were interviewed. Distance had association only with perceived health status. There were no differences between males and females, as well as between age groups and educational attainme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…After including all four determinants in the multiple regression analysis, cognitive dissonance and injunctive norms are no longer significant, leaving only beliefs (p-value = 0.004) and ascription of responsibility (p-value < 0.001) as predictors of commitment, with the latter having a much larger relative importance as measured by the average contribution to the explained variance (RI = 0.473 compared to about them . Assuming participants who hike long distances are likely to have a keen interest in nature (Mayer & Lukács, 2021), our findings offer empirical evidence in support of this interestparadox.…”
Section: Theoretical Determinants Explaining the Effectiveness Of Ple...supporting
confidence: 54%
“…After including all four determinants in the multiple regression analysis, cognitive dissonance and injunctive norms are no longer significant, leaving only beliefs (p-value = 0.004) and ascription of responsibility (p-value < 0.001) as predictors of commitment, with the latter having a much larger relative importance as measured by the average contribution to the explained variance (RI = 0.473 compared to about them . Assuming participants who hike long distances are likely to have a keen interest in nature (Mayer & Lukács, 2021), our findings offer empirical evidence in support of this interestparadox.…”
Section: Theoretical Determinants Explaining the Effectiveness Of Ple...supporting
confidence: 54%
“…The affective relationship with nature nurtures important insight and enhance observational skills and the potential to think (Miller, 2005). Flyfishers, like mountaineers (Dyck et al, 2003) and wild river rafters (Vagias et al, 2005), are motivated to seek challenges in natural environments (Mayer & Luk acs, 2021). Considering work on attraction to situations involving the uncertainty of outcome and novelty (Ewert et al, 2013), it is not surprising that flyfishers seek out environments for optimal arousing encounters, sometimes in a context of competition.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…The dominance by male participants reflects a general male dominance in fishing (Copeland et al, 2017; Magee et al, 2018). Although some studies have not found any differences in the numbers of males and females participating in recreation in wild nature (Di Fabio & Rosen, 2019; Mayer & Lukács, 2021), there is evidence of a higher connection to nature among women (Zhang et al, 2014), which may discourage them from a “blood sport,” a potential interpretation relevant to recreational fishing.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…On the other side, motivation theory is a perspective for us to understand why the SM negatively impact to outdoor recreation intention. According to motivation theory, motivation is a process of directing people to behave in certain way [ 21 , 22 ]. In order to satisfying needs, people would perceive stresses to take actions in certain way.…”
Section: Hypothesis Developmentmentioning
confidence: 99%